Mergers of Public Sector Banks: An Impact - Kempegowda P. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Banking system is considered to be a major sector which pumps money to the business, commercial activities that facilitate the growth of the economy. Banks collects deposits from the public and extends advances to the business activities of the economy. The study aims at understanding and analyzing the process of merger as banking institution plays pivotal role in supplying fiancé into economic activities of the nation and also to what extent the economy is affected by the merging process. The study is taken based on the secondary data which is collected from the related journals, working papers and various websites The study intends to understand the process, causes, advantages and impact of merger of public sector banks on the banking system and economy as a whole. It is found that the merger increased the working efficiencies of banks, reduce operational costs and improve risk management and created a larger capital base, created larger entities and enhanced credit growth and better global competitiveness but the study found that merging has not facilitated the efficient management of non-performing assets to a greater extent due to improper policy to handle the NPAs. Hence the study paper outlines briefly the entire process of merging and its effects on the economy as whole and baking operations.